The influence of the radius of curvature of the knee member on the behavior of knee braced frames - Mohammad Hosein Adibrad; Mina Mortezaie (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
Reducing the irreversible damage caused by earthquakes has always been the ultimate goal for researchers and scientists in earthquake engineering. Knee-braced frames (KBFs) are one of the common lateral load-resisting systems against seismic forces. During a severe earthquake, all frame components remain within the elastic range, while only the knee member enters the plastic range. In previous studies, the knee member was considered a linear element (with an infinite radius of curvature) that acted as a beam when absorbing energy. In the present research, using the ABAQUS finite element software, the radius of curvature of the knee member was reduced, transforming it from a linear element into an arc element. The simultaneous impact of axial force, shear force, and bending moment on energy absorption was examined. The results indicate that in frames with a constant span-to-height ratio, the arched knee member demonstrates better seismic performance compared to the linear knee member, increasing the frame's load-bearing capacity by up to 15%. However, with an increase in the span-to-height ratio, alongside a roughly 40% increase in strength, the likelihood of failure more than doubles.